Environmental Effects on the Seasonal Distribution of an Estuarine Species Neoarius graeffei in Northern New South Wales, Australia - Lauren J. Stoot; Gavin L. Butler; Yuri Niella; Gregory S. Doran; Jason D. Thiem; Matthew D. Taylor; Lee J. Baumgartner (Estuaries and Coasts, 2024)
Coastal river systems provide essential habitats for a diversity of fish species that transition marine, estuarine, and freshwater environments to complete their lifecycles. Movement among and within these environments is important to access resources that optimise growth, survival, and reproduction. Knowledge on the movements, including the drivers, underpins management strategies, although this information is often lacking for many species. We used acoustic telemetry to quantify the relative importance of a range of abiotic stimuli in relation to seasonal movement patterns in blue salmon catfish Neoarius graeffei throughout an unregulated coastal river catchment, the Clarence River in northern New South Wales, Australia. Neoarius graeffei continuously occupied the Clarence River system for the duration of the 1-year study and were mostly confined to estuarine reaches, with occasional movement into freshwater habitats. Seasonal differences in habitat occupation were observed, with N. graeffei using habitats close to the river mouth in winter and upstream estuary habitats in spring. Broad-scale movement patterns were influenced by both water temperature and river flow, and high-flow events (> 1.5 m) resulted in short-term changes (~ 10 days) in habitat use. Sex-specific differences in seasonal habitat use were also observed which we hypothesise is linked to contrasting energetic investment in reproduction. The response of N. graeffei to changes in river flow highlights the need for assessment on these impacts for estuarine-dependent species more broadly, in the face of climate change and increased river regulation.